Face to face: Martin Luther's view of reality - Kolb, Robert (Lutheran quarterly books, 2024)
"Kolb explores Luther's use of the Latin preposition "coram" - "face-to-face" - to demonstrate the foundational role of relationships in Luther's thought. For Luther, believers, fundamentally rooted in their relationship with the Creator of every person and thing, experience all of life's realities in relationship: with God, self, and others"--